An improved petri net for fault analysis of an electronic system with hybrid fault of software and hardware. (February 2021) - Bai, Song; Li, Yan-Feng; Huang, Hong-Zhong; Yu, Aodi; Zeng, Ying
Highlights: Proposing software-hardware hybrid fault in fault analysis of electronic systems. Using an improved Petri net to analyze hybrid fault of electronic systems. A typical electronic system case is provided in this paper. Abstract: With times developing, electronic systems are becoming much more complex due to close interaction between hardware and software within them, and thus accurate fault analysis methods are required in practical engineering. In this paper, the hybrid fault mode of electronic system is proposed, and its characteristics and propagation categories are discussed. To analyze the hybrid fault, a fault analysis framework is given based on an improved Petri net, by which the fault analysis of an engineering case is presented. In the improved method, the interaction of hardware and software is considered in the fault analysis of electronic systems, and is also verified the effectiveness of the proposed method. The results indicate that it is especially effective on qualitative analysis.